Recurrent abdominal pain in adolescents with anxiety and depression disorders - Fastralina Fastralina; Sri Sofyani; M. Joesoef Simbolon; Iskandar Z. Lubis (Indonesian Pediatric Society, 2013)
Background Anxiety and depression disorders in adolescentsmay affect their academic performances and social functioningat school. Adolescents with these disorders sometimes developrecurrent abdominal pain (RAP).Objective To assess the occurence of recurrent abdominal painamong adolescents with anxiety and depression disordersMethods We conducted a cross-sectional study from Augustto September 2009 in 12-18 year-old adolescents from 3 juniorhigh schools and 3 senior high schools in Secanggang Subdistrict,Langkat District, North Sumatera Province. We screened 960adolescents. Subjects were selected by consecutive samplingand instructed to fill the child behavior checklist (CBCL) andchildren's depression inventory (CDI) forms. Those with suspectedanxiety/depression (CBCL score 2: 12 for boys and 2: 14 for girls)and those with suspected depression (CDI score 2: 13) were thenexamined by a psychiatrist. Adolescents diagnosed with anxiety ordepression disorders were instructed to fill the RAP questionnairebased on Apley and Naish criteria.Results From the CBCL and CDI forms, 250 students weresuspected of having anxiety and/or depression. From these,144 students participated in this study. Of the 84 students withanxiety disorders, 60 (71.4%) students suffered from RAP. Ofthe 60 students with depression disorders, 31 (51 %) sufferedfrom RAP.Conclusion Adolescents with anxiety or depression are morelikely to have recurrent abdominal pain.